Biomass energy in China's terrestrial ecosystems: Insights into the nation's sustainable energy supply. (July 2020) - Yan, Pu; Xiao, Chunwang; Xu, Li; Yu, Guirui; Li, Ang; Piao, Shilong; He, Nianpeng
Abstract: The energy stored in biomass, a key component of global sustainable energy, is essential for achieving the United Nations Sustainable Development Goals, especially for climate change mitigation and energy security. However, it remains unknown how much energy is stored in the vegetation biomass of China's terrestrial ecosystems. Furthermore, the shortage of biomass has limited the development of China's bioeconomy and bioenergy industry, requiring us to seek more multi-source and sustainable biomass supplies. In view of this, through comprehensive investigations and systematic data integration (including biomass data, calorific value data, land cover data, climate data, etc.), we explored the gross biomass energy (BE) reserves and their spatiotemporal pattern based on a total of 14 vegetation types that account for 76.24% of China's land area. The theoretical potential of gross BE in China was estimated as 535.91 EJ in 2010, which was equivalent to 18.29 Gt standard coal. BE showed a trend of continuous increase from 1980 to 2060 and is expected to peak in 2030. Importantly, BE (per land area or per capita) was significantly negatively correlated with provincial development levels in China. Our findings indicate that China has abundant BE reserves, which have potential as feedstocks for the production of different forms of energy in the context of sustainable development. Furthermore, more advanced low-cost technologies, such as coal and biomass co-gasification, are expected to promote the transformation and upgradation of energy systems in China in the future. Highlights: Diverse biomass supply ensures sustainable bioenergy without adverse effects on food security and the environment. Biomass energy in China was approximately 535.91 EJ (or 18.29 Gt standard coal), representing a steady increase from 1980 to 2060. A negative correlation between biomass energy and provincial development level highlights the importance of effective compensation policies for sustainability. Ample biomass is vital in scenarios of upgrading energy and stimulating green economic growth in China.